Tax Optimization for Small and Medium-sized Companies (SMCs). Perspectives from Agency, Transaction Costs and Game Theories - BENDRIOUCH , Mohammed (Revue Internationale des Sciences de Gestion, 2024)
Taxation is seen as an instrument or a tool of economic policy for the state, which is used in different manners. Taxation is also an instrument of SMCs management policy. Previously, taxation was previously considered a burden and an obstacle that it was advisable to undergo passively, while now, in modern management and governance theory, taxation is recognized as a key parameter in business management. The choices made in the quest of optimization raise concerns about what can be accepted without negatively impacting public finances. We intend to present a literature review that includes theories relevant to this issue, specifically the Theory of Agency, Transaction Cost Theory and the Theory of Games.